Periodic Solutions and Exponential Stability of a Class of Neural Networks with Time-Varying Delays - Yingxin Guo; Mingzhi Xue (Discrete Dynamics in Nature and Society)
Employing fixed point theorem, we make a further investigation of a class of neural networks with delays in this paper. A family of sufficient conditions is given for checking global exponential stability. These results have important leading significance in the design and applications of globally stable neural networks with delays. Our results extend and improve some earlier publications.